2020
DOI: 10.2147/dddt.s241066
|View full text |Cite
|
Sign up to set email alerts
|

<p>Experimental Study on the Role of Apelin-13 in Alleviating Spinal Cord Ischemia Reperfusion Injury Through Suppressing Autophagy</p>

Abstract: Background: This study aimed to explore the effect of Apelin-13 in protecting rats against spinal cord ischemia reperfusion injury (SCIR), as well as the related molecular mechanisms. Methods: One week prior to the experiment, experimental Sprague-Dawley rats were injected with Apelin-13 and the autophagy activator rapamycin through the tail vein once a day for 7 consecutive days. The SCIR rat model was prepared through the abdominal aorta clamping method. At 72 h after injury, the spinal cord tissue water con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Patients who have undergone thoracic and abdominal aortic surgery are frequently faced with nerve injury induced by spinal cord ischemia, which is driven by ROS-induced neuronal apoptosis, neuroinflammation, and autophagy [157]. The intraperitoneal injection of apelin-13 exerted spinal cord protection and recovery of motor function in rats by suppressing autophagy, oxidative stress, and mitochondrial dysfunction [158].…”
Section: Oxidative Stress In the Central Nervous Systemmentioning
confidence: 99%
“…Patients who have undergone thoracic and abdominal aortic surgery are frequently faced with nerve injury induced by spinal cord ischemia, which is driven by ROS-induced neuronal apoptosis, neuroinflammation, and autophagy [157]. The intraperitoneal injection of apelin-13 exerted spinal cord protection and recovery of motor function in rats by suppressing autophagy, oxidative stress, and mitochondrial dysfunction [158].…”
Section: Oxidative Stress In the Central Nervous Systemmentioning
confidence: 99%
“…A case report by Clanton et al in 1999 revealed that erythromycin lactobionate, a macrolide with gastrointestinal prokinetic properties, can be used for management of refractory gastroparesis induced by SCI [75]. Later, it was shown that erythromycin exerts neuroprotective effects in rodents and swine undergoing cerebral ischemia–reperfusion [76,77]. In a model of cerebral ischemia–reperfusion injury, it was also indicated that erythromycin significantly reduces oxidative stress and pro‐inflammatory cytokines (e.g., TNF‐α) as well as Ca 2+ ‐binding adapter molecule 1 (IBA‐1) which represents inflammatory microglial activity [51,78].…”
Section: Antibiotics With Therapeutic Effects In Scimentioning
confidence: 99%
“…It also inhibits mitochondrial protein synthesis in different micro‐organisms such as yeasts [80] and human cells [81]. Considering erythromycin’s anti‐inflammatory and neuroprotective effects and its similar structure with other neuroprotective macrolides (i.e., AZM), investigation, and elucidation of its potential effects on mitochondrial dysfunction and microglial polarization in SCI would be interesting [69,77,82].…”
Section: Antibiotics With Therapeutic Effects In Scimentioning
confidence: 99%
“…Spinal cord ischemia reperfusion injury (SCII) is a complication occurring under thoracoabdominal aortic or spinal cord surgery, which brings the risk of paralysis and paraplegia (Li et al, 2015a;Xu & Li, 2020). Although various measures were developed and applied to reduce the risks and improve the outcomes of SCII, satisfactory therapeutic…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord ischemia reperfusion injury (SCII) is a complication occurring under thoracoabdominal aortic or spinal cord surgery, which brings the risk of paralysis and paraplegia ( Li et al, 2015a ; Xu & Li, 2020 ). Although various measures were developed and applied to reduce the risks and improve the outcomes of SCII, satisfactory therapeutic effects still not be achieved due to multifactorial pathogenic factors ( Ege et al, 2004 ; Fang et al, 2015 ; Li et al, 2014a ; Li et al, 2014b ; Zhou et al, 2013b ).…”
Section: Introductionmentioning
confidence: 99%